Geothermal Waters from the Alpine Mountain Region, Europe: A Comprehensive Geochemical and Isotopic Analysis - Cornelia Victoria Anghel; Glenaldo Achmad Zhafran Evito; Mikael Syväjärvi (CV FOUNDAE, 2024)
The Alpine region of Europe, which covers several countries including France, Switzerland, Italy, Austria and Germany, is characterised by its complex geology and significant geothermal potential. This research investigates the geochemical characteristics of geothermal water in the Alpine region, focusing on understanding the origin, evolution, and potential applications of these geothermal resources. Through comprehensive hydrochemical and isotopic analyses, we have identified key geochemical signatures that distinguish the various geothermal systems in the region. The results show that these geothermal waters are mainly influenced by deep magmatic processes, extensive water-rock interactions, and mixing of meteoric and magmatic fluids. Elevated concentrations of elements such as sodium (Na), lithium (Li), and chloride (Cl), as well as different stable isotopes, provide insights into the thermal and geochemical environments of geothermal reservoirs. Based on isotopic analysis oxygen (δ¹⁸O) and hydrogen (δ²H), the most of the geothermal water in the Alpine mountain region of Europe is of meteoric origin (derived from meteoric waters). The isotopic composition can reveal the mixing between meteoric and magmatic water. Intermediate values between GMWL and magmatic water compositions indicate such mixing, helping to understand the fluid dynamics within geothermal systems. This research underlines the importance of integrating geochemical studies in the exploration and management of geothermal resources in tectonically active regions such as the Alps.